Integrating biomechanics at the elite level: The tennis Australian experience - Reid, M.; Whiteside, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Technical skill is key to tennis success. Qualitative critiques of technique are commonplace in the sport. The use of quantitative biomechanics analysis in aiding athlete development has been limited in tennis however, owing largely to its cost, the expertise required for implementation and/or the timeliness of meaningful feedback. Tennis Australia has nevertheless attempted to strategically deploy quantitative biomechanics analysis, often doubling as research opportunities, to facilitate a coach`s understanding of specific parts of his/her athlete`s technique. The organisation has also identified key research questions to improve the sport`s understanding of technique, skill development and injury prevention, generally through the use of motion analysis systems like VICON. The current paper provides some examples of the genesis and outcomes of this research in specific relation to the tennis serve.